Modern drama in theory and practice volume 3: expressionism and epic theatre - Styan, J. L. (New York Cambridge University Press, 1981)
Büchner is the forerunner of expression, followed by Wedekind and Strindberg. The style is then traced from Kaiser and Toller to O'Neill, Wilder and the later O'Casey. Important producers are Reinhardt and Meyerhold. Epic theatre is studied from Piscator and Brecht to Dürrenmatt and Weiss, Arden and Bond, and is seen as flourishing in offshoots of documentary theatre. This book was first published in 1981.